Interaction of Carbon Dioxide with Silver Zeolites - Jürg Baumann; Robert Beer; Gion Calzaferri (CHIMIA)
Photooxidation of water to O2 and of Cl⊖ to Cl2 by Ag⊕-exchanged zeolite A is briefly reviewed. Thermodynamic considerations concerning the free energy storage during these reactions are given. Interaction of CO2 with Ag⊕-exchanged zeolite A of various Ag⊕ content, in the original and partially reduced state, is probed by in situ FTIR transmission spectroscopy. Chemisorbed, carbonate-like species are found in samples of low silver content. The CO2 physisorption capacity is lowest for highly Ag⊕-exchanged samples. After removing the physisorbed CO2 by evacuation, a small amount of weakly bound CO2 remains in the zeolite. Its ν3 (asymmetric stretching) frequency is cation dependent, reflecting some specific interaction with the cations. On chemical reduction of the Ag⊕, the amount of weakly bound CO2 markedly increases, accompanied by spectral changes of the ν3 band of CO2.